Lake effect : a novel [compact disc, unabridged] - Sweeney, Cynthia D'Aprix (HarperAudio, 2026)
It's 1977 and an air of restlessness has settled on the residents of Cambridge Road in Rochester, New York. When Nina Larkin is given a copy of The Joy of Sex by her newly divorced friend, she can no longer dismiss the nearly nonexistent intimacy of her marriage. An intoxicating fling with a prominent neighbor brings Nina a freedom she never thought possible, but also risks the reputations of both families and unravels her daughter Clara's world, just as she stands on the threshold of adulthood. Years later, Clara, now a successful food stylist in New York City, has never been able to move past the long-ago scandal. Drawn back home by the pull of a family wedding and wrestling with her own demons, she makes a pivotal decision that turns her life upside down.